Analysis of the Variation Characteristics of Rock Mechanical Parameters and Slope Stability Under Freeze-Thaw Cycles - Wenhui Tan; Zelong Li; Zhentao Li; Em Sothy; Siying Wu; Qifeng Guo (Applied Sciences)
In high-altitude cold regions, significant diurnal and seasonal temperature variations intensify freeze-thaw damage to rocks, critically impacting slope stability. This study examines a Xinjiang mine slope to assess freeze-thaw effects through laboratory experiments on three lithologies under varying freeze-thaw cycles. Mechanical parameters were determined via the Hoek–Brown criterion, and FLAC3D simulations analyzed stress-deformation characteristics and safety factor trends, validated against field monitoring. After 90 cycles, the results show progressive degradation: uniaxial compressive strength declined by 29.7–45.8%, elastic modulus by 42.7–63.3%, Poisson’s ratio by 16.0–42.1%, cohesion by 71.7–77.1%, internal friction angle by ~52.0%, and tensile strength by 79.3–83.6%. The slope safety factor decreased exponentially (44.5% reduction). Both simulations and monitoring revealed “step-like” displacement growth, with minor discrepancies attributed to modeling assumptions. These findings provide critical insights for safe mining operations in cold regions, highlighting the severe mechanical deterioration induced by freeze-thaw cycles and its implications for slope stability.